Transcatheter Arterial Chemoembolization of Hepatocellular Carcinoma as a Bridge to Liver Transplantation: A Retrospective Study - Antoine Bouchard-Fortier; Réal Lapointe; Pierre Perreault; Louis Bouchard; Gilles Pomier-Layrargues (International Journal of Hepatology)
Background. Transcatheter arterial lipiodol chemoembolization (TACE) can be used in cirrhotic patients with hepatocellular carcinoma to avoid tumor progression before transplantation. Objective. To evaluate the efficacy and safety of TACE used as a bridge to liver transplantation. Methods. TACE was performed in 30 cirrhotic patients with hepatocellular carcinoma. Milan criteria were used to select patients for transplant. Patients had a good or moderately impaired liver function, no arterioportal fistulae, and a good portal perfusion. Results. 48 TACE were performed in 30 patients. Before transplantation, 4 patients were dropped off the list due to tumor extension or liver failure. Complete necrosis of the tumor was observed in 11 patients and partial necrosis in 15 patients. After transplantation, 6 patients died and tumor recurrence was observed in 5 patients with a tumor beyond Milan criteria or no response to TACE. Conclusion. TACE is useful as a bridge to liver transplantation in a selected group of cirrhotic patients with hepatocellular carcinoma. A combined therapeutic approach before surgery might improve the prognosis in these patients.